COVID-19: EPIDEMIOLOGY, PATHOGENICITY AND GLOBAL UPDATES - SINGH, MANJINDER; NAGPAL, MANJU; SINGH, VARINDER; SHARMA, AMEYA; DHINGRA, GITIKA ARORA; MAMAN, PARAMJOT; PURI, VIVEK (International Journal of Applied Pharmaceutics, 2020)
Novel coronavirus (COVID-19) is a highly contagious virus that originated from China and has become a major threat in the current time. Presently, finding an effective treatment strategy for COVID-19 is in infancy. Worldwide, numerous clinical trials employing different treatment strategies (antiviral drugs and vaccines) are in progress to develop an effective therapeutic regimen against COVID-19. Literature related to the epidemiology, mortality, pathogenicity, treatment strategies and clinical data was studied and database was collected using various search engines such as j-gate, google scholar, scihub, pubmed, sciencedirect etc. The present review systematically summarises the published information about epidemiology, various stages of pandemic, mortality, pathogenicity, modes of transmission, clinical characteristics, methods of prevention, ongoing treatment strategies and drugs under clinical trials associated with COVID-19 with a hope to avoid possible threatening of the lives of millions of human beings and provide directions for future studies.